Nowa koncepcja rachunku kosztów działań -time driven ABC - Kostrzewski, Grzegorz (New concept of activity based costing - time driven activity based costing, 2006)
The traditional ABC model for many organizations was hard to implement due to the high costs incurred to interview and survey people for the initial ABC model. An alternative approach for estimating an ABC model, which was called by its inventors (Steven R. Andersson and Robert S. Kaplan) “time-driven activity-based costing”, addresses all the above limitations. The new Time- -driven ABC characterizes with unique approach based on the time equations, which are helpful in estimating the time spent on a particular activity for a specific cost object.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 203-208